Intervenciones de enfermería en el manejo de la terapia del dolor en el área postquirúrgica Hospital General IESS Babahoyo, octubre 2024 – mayo 2025. - Icaza Jurado, Rubí Elizabeth (2025)
The activities performed by nursing staff to prevent pain in postoperative patients are essential to ensuring recovery. Postoperative pain is a highly complex physiological reaction that occurs after surgery. This varies depending on the type of pain the patient experiences, whether surgical or personal. A visual analog scale (VAS), with a 10-cm line, is used to measure the level of pain, indicating a value from 1 to 10, reflecting the pain experienced. The interventions provided by nursing staff are very important for the quality and compassionate care of patients after surgery.